THE SIGNIFICANCE OF FORMING PSYCHODIAGNOSTIC COMPETENCIES IN PRIMARY CLASS TEACHERS (Web of Teachers: Inderscience Research, 2024)
The article talks about the importance of forming psychodiagnostic competencies in primary school teachers.